2018
DOI: 10.1186/s12870-018-1311-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of nonchilled, chilled, and late-pink bud reveals flowering pathway genes involved in chilling-mediated flowering in blueberry

Abstract: BackgroundBlueberry cultivars require a fixed quantity of chilling hours during winter endo-dormancy for vernalization. In this study, transcriptome analysis using RNA sequencing data from nonchilled, chilled, and late pink buds of southern highbush blueberry ‘Legacy’ was performed to reveal genes associated with chilling accumulation and bud break.ResultsFully chilled ‘Legacy’ plants flowered normally whereas nonchilled plants could not flower. Compared to nonchilled flower buds, chilled flower buds showed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 51 publications
(67 reference statements)
6
57
0
Order By: Relevance
“…Studies on transcriptome regulation based on phenotypes is a powerful research method [29,30]. Using this analytical method, DEGs and related regulatory pathways produced by Asiatic lily and tropical lotus during vernalization have been investigated [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on transcriptome regulation based on phenotypes is a powerful research method [29,30]. Using this analytical method, DEGs and related regulatory pathways produced by Asiatic lily and tropical lotus during vernalization have been investigated [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that the openness of flower buds in woody plants was related to dormancy release [13][14][15]. Before the spring flowering of 'Changchun', the long dormancy process of flower buds was released, and the growth amount increased significantly.…”
Section: Flowering Initiation Is An Important Stage During 'Changchunmentioning
confidence: 96%
“…The increased level of PpEBB (EARLY BUD-BREAK) induced high levels of transcription of four PpCYCD3 (D-type CYCLIN) genes, which promoted cell division and resulted in a significant increase in the primordia size of Pyrus pyrifolia 'Kosui' lateral flower buds [14]. The profile of differentially expressed genes (DEGs) suggests that orthologs of FT, FD, TFL1 (TERMINAL FLOWER 1), LFY (LEAFY), and MADS-box genes were the major genes involved in chilling-mediated Vaccinium corymbosum bud-break [15]. Obviously, the identification of genes associated with flowering and dormancy release was due to the comparison of reproductive organs in different seasons.…”
mentioning
confidence: 99%
“…Working in an antagonistic manner to VRN1 and VIN3, which downregulate repressors of endodormancy release, are FRIGIDA 4 and CONSTANS-like genes. Increased expression and activity of FRIGIDA 4 results in increased activity of repressors of endodormancy release, such as Flowering Locus C (FLC), in Arabidopsis [64] and blueberry [65]. FRIGIDA 4 decreased significantly in expression throughout conditioning in 'Bartlett', suggesting that its downregulation may correspond to decreased activation of ripening repressors in a role homologous to regulation of flowering time (Figure 4).…”
Section: Cold and Temperature Stress-induced Processesmentioning
confidence: 99%